Research on genre learning for re-imagining the pedagogy of writers’ retreats - Paxton, M. (South African Journal of Higher Education, 2017)
Writers’ retreats were originally conceived of as quiet spaces away from the workplace where academic staff would have uninterrupted time to focus on writing. Recently, however, the literature has referred to “structured retreats” (Murray 2010:102) which allow for “information giving” (pedagogy) and participants’ discussion of writing in progress.